Circovirus porcino tipo 3: impacto y perspectivas en sanidad porcina - Melisa Negrelli Pilar; Maria Alejandra Quiroga; Carlos Juan Perfumo; Mariana Alejandra Machuca (Analecta Veterinaria, 2026)
Circoviruses are single-stranded, circular DNA viruses that belong to the family Circoviridae and the genus Circovirus. In 2016, porcine circovirus 3 (PCV3) was identified in the United States for the first time, associated with a clinical presentation that resembled porcine dermatitis and nephropathy syndrome. Since then, much research has been done in different parts of the world. Experimental studies have shown that PCV3 infection can be subclinical or associated with various diseases. The most characteristic lesions include vasculitis and perivasculitis, mainly affecting the heart and kidneys. In addition, frequent concurrent infections with other pathogens have been reported, complicating clinical interpretation. Diagnosis of PCV3 is based on clinical findings, molecular viral detection techniques, and identification of microscopic lesions. However, additional experimental models are still required to understand its pathogenesis. Although PCV3 shares certain similarities with PCV2, its clinical and epidemiological impact remains under investigation. Emerging evidence highlights its potential involvement in complex porcine diseases. This study compiles and analyzes current information regarding the pathogenesis, clinical manifestations, and diagnostic methods related to PCV3.